Systematic Literature Review: Education for Sustainable Development (ESD) in Science Learning to Develop 21st Century Skills - Salsabila, Nabila Adawiyah Nur; Trisnowati, Eli; Juliyanto, Eko (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
The 21st century demands that learners not only master knowledge, but also critical, creative, collaborative, and communicative thinking skills in response to the global challenges of the industrial revolution era 4.0. However, these skills have not been optimally developed in science learning because learning practices remain teacher-centered and do not provide space for high-level thinking activities that address the low abilities of the 21st century. On the other hand, increasing environmental, social, and economic problems underscore the need for education that fosters sustainability awareness. Education for Sustainable Development (ESD) is a potential approach to integrating 21st-century skills and sustainability values in science learning. However, the implementation of ESD in Indonesia remains limited. It has not been entirely directed toward strengthening 21st-century skills, so a more in-depth study is needed to assess the extent to which ESD has been applied in science learning and its contribution to the development of these competencies. This study aims to analyze the implementation of ESD in science learning to develop 21st-century skills in Indonesia through a Systematic Literature Review of 25 published articles from Google Scholar, Semantic Scholar, and ResearchGate, published between 2020 and August 26, 2025. The article selection process followed the inclusion and exclusion criteria and guidelines of PRISMA 2020, resulting in 25 studies deemed appropriate and relevant. The results of the analysis show that the application of ESD in science learning focuses on developing tools aligned with the learning models used, including Problem-Based Learning (PBL), Project-Based Learning (PjBL), Predict–Observe-Explain (POE), RADEC, and SSCS. The PBL model is the most dominant one because it effectively encourages students to analyze and solve environmental problems scientifically. In addition, most of the research uses e-modules, ESD-based LKPDs, digital media, and virtual field trips as learning media. Based on the analysis of 21st-century skills, critical thinking is the most improved competency (48.3%), followed by sustainability awareness and problem-solving (13.8%), creative thinking and science literacy (10.3%), and environmental literacy (3.4%). ESD integration has been proven to strengthen students’ ability to analyze phenomena, evaluate solutions, and make sustainability-oriented decisions. The material topics most often associated with ESD include Environment and Sustainability (44.8%) and Energy and Force (34.5%), reflecting the relevance of climate change, ecosystem, and renewable energy issues in science learning.